2021
DOI: 10.3847/1538-4357/abc9ba
|View full text |Cite
|
Sign up to set email alerts
|

The TW Hya Rosetta Stone Project. II. Spatially Resolved Emission of Formaldehyde Hints at Low-temperature Gas-phase Formation

Abstract: Formaldehyde (H 2 CO) is an important precursor to organics like methanol (CH 3 OH). It is important to understand the conditions that produce H 2 CO and prebiotic molecules during star and planet formation. H 2 CO possesses both gas-phase and solid-state formation pathways, involving either UV-produced radical precursors or CO ice and cold (20 K) dust grains. To understand which pathway dominates, gaseous H 2 COʼs ortho-to-para ratio (OPR) has been used as a probe, with a value of 3 indicating "warm" conditi… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
14
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
5
5

Relationship

6
4

Authors

Journals

citations
Cited by 27 publications
(16 citation statements)
references
References 67 publications
2
14
0
Order By: Relevance
“…Higher temperatures are found for the inner regions, however the snr of the data is low, as reflected by the large inferred uncertainties. Column densities across the 0.5 − 2 interval range between 4 × 10 12 − 4 × 10 13 cm −2 , in line with other protoplanetary disks (e.g., Pegues et al 2020;Terwisscha van Scheltinga et al 2021). A peak optical depth of ∼ 0.1 is derived for the 3 03 -2 20 transition, with the weaker transition showing a factor of ∼ 10 lower optical depth.…”
Section: H 2 Cosupporting
confidence: 78%
“…Higher temperatures are found for the inner regions, however the snr of the data is low, as reflected by the large inferred uncertainties. Column densities across the 0.5 − 2 interval range between 4 × 10 12 − 4 × 10 13 cm −2 , in line with other protoplanetary disks (e.g., Pegues et al 2020;Terwisscha van Scheltinga et al 2021). A peak optical depth of ∼ 0.1 is derived for the 3 03 -2 20 transition, with the weaker transition showing a factor of ∼ 10 lower optical depth.…”
Section: H 2 Cosupporting
confidence: 78%
“…The temperature of the (outer) disk midplane is derived from the location of the snowlines of major species such as H 2 O and CO (Mathews et al 2013;Qi et al 2013;van 't Hoff et al 2017van 't Hoff et al , 2018Qi et al 2019;Leemker et al 2021). Additionally rotational diagrams are used to derive the temperature of intermediate layers in disks (e.g., Schwarz et al 2016;Loomis et al 2018;Pegues et al 2020;Terwisscha van Scheltinga et al 2021). In this work, we study the rarely observed J = 6 − 5 transition of 13 CO (E u = 111.1 K) in two transition disks: LkCa15 and HD 169142 with spatially resolved ALMA data.…”
Section: Introductionmentioning
confidence: 99%
“…The distribution of H 2 CO suggests that the bulk of the observed H 2 CO in the disc is formed via gas-phase reactions. This is indicated both by the o/p ratios measured in TW Hya (Terwisscha van Scheltinga et al, 2021) and by the vertical distribution of molecular emission in the edge-on disc of IRAS 04302 where H 2 CO mostly arises from an intermediate disc layer, the so called molecular layer (Podio et al, 2020b;van't Hoff et al, 2020). However, for IRAS 04302 H 2 CO emission is detected also in the outer disc midplane, where molecules are expected to be frozen onto the dust grain icy mantles.…”
Section: Organics As C-o-n Carriersmentioning
confidence: 77%